Improving Participation and Learning Result Through Make A Match Model of IPS Lessons - Syarifuddin Syarifuddin; Mas'ati Ruhing Hasan; Hamka Hasan (UNM Geographic Journal, 2018)
The purpose of this reseach is to increase the students’ participation and learning result of Class VIII.c SMP Negeri 23 Simbang on IPS subjects. This type of research was a classroom action research. Data collection techniques used students' participant observation sheets, evaluation of learning outcomes, documentation, and field notes. The research was hold in 2 cycles with the main subject was population. Each cycle included four stages: (i) planning (ii) implementation of action (iii) observation (iv) reflection. Data were analyzed by using qualitative and quantitative descriptive analysis. The result of the research shows that the students’ participations had increased classically from the beginning of the cycle I until the end of cycle II, ranging from 50% to 80.8% passed the the criteria of 75% as the high category that had been  established. While the students’ learning result classically also increased from 57.7% at the beginning of the first cycle to 84.6% at the end of cycle II,it means that the result has passed the classical learning completion that was defined by 80% as the high category. It can be concluded that the implementation of the Make a Match learning model can improve the students’ participation and learning result of class VIII.c SMP Negeri 23 Simbang on Social Studies subjects.Penelitian bertujuan untuk meningkatkan partisipasi dan hasil belajar peserta didik Kelas VIII.c SMP Negeri 23 Simbang pada mata pelajaran IPS. Jenis penelitian ini adalah penelitian tindakan kelas. Teknik pengumpulan data menggunakan lembar observasi partisipasi peserta didik, lembar evaluasi hasil belajar, dokumentasi, dan catatan lapangan. Pembelajaran dilaksanakan sebanyak 2 siklus dengan materi pokok kependudukan. Setiap siklus meliputi 4 tahap: (i) perencanaan (ii) pelaksanaan tindakan (iii) observasi (iv) refleksi. Data dianalisis dengan menggunakan analisis deskriptif kualitatif dan kuantitatif. Hasil  penelitian menunjukkan partisipasi peserta didik secara klasikal diawal siklus I sampai diakhir siklus II mengalami peningkatan, mulai dari angka 50% sampai dengan 80,8% melewati syarat keberhasilan yang ditetapkan yaitu 75% dengan kategori tinggi. Sedangkan hasil belajar  peserta didik secara klasikal juga mengalami peningkatan dari angka 57,7% diawal siklus I menjadi 84,6% diakhir siklus II, artinya sudah melewati syarat ketuntasan belajar klasikal yang ditetapkan yaitu 80% dengan kategori tinggi. Dapat disimpulkan bahwa penerapan model pembelajaran Make a Match dapat meningkatkan partisipasi dan hasil belajar peserta didik kelas VIII.c SMP Negeri 23 Simbang pada mata pelajaran IPS.